Pembagian Warisan Berdasarkan Sistem Bilateral Perspektif Ulama’ Kontemporer - Bustomy , Ahmad Ainur; Umam, M. Nur Khotibul (Al-Qadlaya : Jurnal Hukum Keluarga Islam, 2022)
This research focuses on the distribution of inheritance based on the bilateral system. Inheritance law is part of family law that plays a very important role, as it both determines and reflects the kinship system that prevails in society. In Java, this interrelation is known as “Islam Jawa” (Javanese Islam), because the syncretism between Islam and tradition (adat) gave rise to a tradition referred to as kejawen. This condition demonstrates that in Java, adat and religion are not markedly different; in fact, at times they are difficult to distinguish or separate, as they appear to have merged. Consequently, in matters of inheritance law, compromises between customary law and Islamic law inevitably emerge.The emphasis of this study lies in the concept of inheritance distribution based on the bilateral system from the perspective of customary law and the views of contemporary Islamic scholars. The main objective of this research is to analyze the concept of bilateral inheritance distribution found in customary law and in the opinions of contemporary scholars. This study employs a normative juridical approach. Most of the primary data are drawn from library research consisting of the latest scientific literature, newly developed understandings of established facts, and new ideas. The scope of the study includes the Qur’an, contemporary scholars’ opinions, and academic journals discussing bilateral inheritance. The stages of data analysis include editing, classifying, verifying, analyzing, and concluding. To ensure the credibility of the research as a scientific work, data validity was tested through credibility and dependability assessments. The findings of this research conclude that inheritance distribution based on the bilateral system emphasizes an equal division of inheritance between men and women. The bilateral approach prioritizes a 1:1 ratio, which can reduce inequality compared to the 2:1 ratio. Furthermore, according to contemporary scholars, provided that the heirs consent, the bilateral 1:1 concept may be justified as being fairer in modern contexts. This is due to the changing roles of women in contemporary times, where many women take on responsibilities as breadwinners, unlike women in the classical era.